Linear approximation of approximately linear functions - Vestfrid, Igor A. (Aequationes mathematicae, 2003)
Ulam posed the problem: "Give conditions in order for a linear mapping near an approximately linear mapping to exist". In this spirit we investigate the stability (local and global) of Jensen's functional equation and approximate (in the spirit of John) epsilon-rigid maps, epsilon-isometries and epsilon-quasi-isometries by affine near isometries. In this way we extend one of John's theorems. [PUBLICATION ABSTRACT]